2017
DOI: 10.3906/tar-1703-103
|View full text |Cite
|
Sign up to set email alerts
|

Response of five triticale genotypes to salt stress in in vitro culture

Abstract: Different techniques have been suggested to protect plants from environmental stress. Therefore, new techniques should be developed to produce salt-resistant genotypes. Selection and improvement of desirable genotypes for this objective require suitable screening methods. Tissue culture can help in the efforts to produce new cultivars against environmental stress factors. In addition, in vitro culture studies permit relatively faster responses, shorter generation time, and regular environmental conditions as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 44 publications
(60 reference statements)
1
20
0
Order By: Relevance
“…In the perspective of understanding glyoxalase pathway genes in stress defensive mechanisms, we performed real-time quantification experiments, physiological assays and in silico characterization for all the deduced proteins of glyoxalase genes (glyoxalase I, II and III) isolated from E. arundinaceus and commercial sugarcane hybrid. In vitro method of quantifying the salinity tolerance level is a familiar and successful technique for different plant species [22]. Even though the level of tolerant mechanisms differs from in vitro to in vivo, conditions have been successfully applied for many plant species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the perspective of understanding glyoxalase pathway genes in stress defensive mechanisms, we performed real-time quantification experiments, physiological assays and in silico characterization for all the deduced proteins of glyoxalase genes (glyoxalase I, II and III) isolated from E. arundinaceus and commercial sugarcane hybrid. In vitro method of quantifying the salinity tolerance level is a familiar and successful technique for different plant species [22]. Even though the level of tolerant mechanisms differs from in vitro to in vivo, conditions have been successfully applied for many plant species.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro method of quantifying the salinity tolerance level is a familiar and successful technique for different plant species [ 22 ]. Even though the level of tolerant mechanisms differs from in vitro to in vivo, conditions have been successfully applied for many plant species.…”
Section: Discussionmentioning
confidence: 99%
“…1). Using in vitro callus cultures, several researchers analyzed salt-stress-induced differential antioxidant activities in callus of different plant species such as Sugarcane (Patade et al 2012), Melon (Kusvuran et al 2016), and Triticale (Bezirganoglu 2017). The Gujosoya-2 and SL-295 genotypes were unable to maintain higher enzymatic antioxidant activities to cope with Na + stress.…”
Section: Discussionmentioning
confidence: 99%
“…In Medicago, Lotus, Faba bean, Barley, Chrysanthemum, Cucumber, and rice, it has been shown that controlled chloride transport and exclusion from shoot are well correlated (Sibole et al 2003;Teakle et al 2007;Tavakkoli et al 2010Tavakkoli et al , 2011Guan et al 2012;Huang et al 2015;Khare et al 2015). Most of the studies at cellular level have been carried out in the presence of NaCl salt (Rahnama et al 2003;Rahnama and Ebrahimzadeh 2004;Kusvuran et al 2016;Bezirganoglu 2017), but very meager information is available using individual Na + or Cl − salts. In vitro culture techniques offer a significant tool to evaluate genotypes for salt tolerance in less time and space at cellular level under uniform and controlled growth and treatment conditions (Nikam et al 2014;Piwowarczyk et al 2016;Bezirganoglu 2017;Boamponsem et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation